Desulfurization of sulfur compounds in diesel oil through oxidation, adsorption and sulfone destruction - Choi, Angelo Earvin S. (Animo Repository, 2016)
Fossil fuel derived oil is needed to be treated through a desulfurization process in order for it to comply with stringent environmental regulations. In this study, an oxidative desulfurization with the use of an ultrasound probe and a high shear mixer together with a polyoxometalate/H2O2 systems, clay material adsorbents for adsorption and Fentons reagent for sulfone destruction was investigated. Under the ultrasound-assisted oxidative desulfurization (UAOD) process, significant factors such as ultrasound time (6 30 min), amplitude (20 60%), catalyst dosage (10 500 mg) and reaction temperature (30 70 C) on sulfur conversion was studied. While in the mixing-assisted oxidative desulfurization (MAOD) process significant factors tested was the effect of mixing time (6 30 min), catalyst dosage (10 500 mg), H2O2 concentration (30 50 %v/v) and reaction temperature (30 70 C) on sulfur conversion was examined. For the batch adsorption process, results indicate that the significant parameters include pH (1 5), adsorbent dose (1 5g) and temperature (25 55 C). Sulfone destruction experiments that were tested include H2O2 dosage (50 -250 mM), Fe2+ dosage (8 40 mM) and pH (1 5). These factors were subjected to a Box-Behnken design under response surface methodology in order to optimize the operating conditions as well as determining the level of significance of each single and interacting factor using the analysis of variance. Results showed that the optimized condition in the oxidation process of UAOD and MAOD showed 94.96% and 96.64% sulfur conversion, respectively, while the batch adsorption process showed 91.89% sulfur reduction. Results showed that the optimized condition in benzothiophene sulfone and dibenzothiophene sulfone under the Fenton process showed 70.14% and 55.58% sulfone destruction, respectively.